Konsumsi Cokelat Hitam Untuk Mencegah Preeklampsia - Lyliani Khairunnisa (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background :Preeclampsia is a complication of pregnancy that has a high mortality and morbidity rate. Preeclampsia is characterized by new onset gestational hypertension and proteinuria. One theory regarding the mechanism of preeclampsia is endothelial dysfunction. Endothelial dysfunction causes decreased levels of nitric oxide. Objective :To find out more about consumption of dark chocolate to prevent preeclampsia Methods :Using literature studies from both national and international journals by summarizing the topic of discussion and comparing the results presented in the article. Results :Dark chocolate has high levels of flavonoids. Flavonoids in dark chocolate can help to increase levels of nitric oxide thus preventing endothelial dysfunction. Conclusion :Consumption of dark chocolate can prevent preeclampsia.